TINJAUAN POLITIK DAN SYARIAH TERHADAP KEBIJAKAN PEMINDAHAN IBU KOTA NEGARA SEBAGAI PILIHAN RASIONAL - Yudha Alam, Wira (Jurnal Ekonomika dan Bisnis Islam, 2023)
The movement of the IKN has been a plan since Joko Widodo was elected president, in 2019. This article seeks to explore the policy of the State Capital (IKN) understood as the path taken by the government. Using a rational choice framework in the perspective of sharia and politics. This policy exists because it is supported by three aspects: first, the environmental aspect which is a stimulus for actors to act. Second, aspects of the rules of the game through a legal-formal framework that makes it easy to provide the red carpet for actors. Third, the organizational aspect that emphasizes the self-interest of the actors so that it creates a desire to shape IKN policies. This study uses a qualitative method with an analytical descriptive approach, which analyzes various available data. The discussion put forward is based on references examined through the opinions of experts and scholars, as well as from books. The transfer of IKN is considered to tend only as a policy that benefits certain groups, and is considered to have not achieved benefit, because benefit concerns the interests of many people, not personal interests or certain small groups